The sea serpent and me - Slater, Dashka; Chien, Catia (Boston : Houghton Mifflin, 2008)
A small sea serpent falls from the faucet into a bathtub and becomes a little girl's best friend, but as he grows, they both realize that he needs to go back to the sea where he belongs.
Wilson's Children, October 2010.
School Library Journal, June 2008.
Horn Book, October 2008.
Kirkus Review, April 2008.
Wilson's Children.
School Library Journal.
Keywords: Sea monsters -- Juvenile fiction; Growth -- Juvenile fiction; Sea monsters -- Fiction; Growth -- Fiction; Sea monsters -- Fiction; Growth -- Fiction; Sea monsters -- Fiction; Growth -- Fiction